2008
DOI: 10.1080/03630240802575179
|View full text |Cite
|
Sign up to set email alerts
|

The Menstrual Cycle and Sexual Behavior: Relationship to Eating, Exercise, Sleep, and Health Patterns

Abstract: Patterns of eating, exercise, sleep and health were investigated across 180 menstrual cycles of 89 women who engaged in sex with a male (n = 45; cycles = 85), a female (n = 21; cycles = 37) or abstained from sex (n = 33; cycles = 58) from January 2005 to December 2007 (10 contributed to 2 groups). Cycles were divided into 5 phases based on their luteinizing hormone surges. Daily questionnaires and saliva for IgA and cortisol analyses were obtained. Women indicated that they ate more (p < .008) and did not slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 30 publications
(44 reference statements)
2
44
0
3
Order By: Relevance
“…Some researchers employed physiological measurements to determine the LH surge (e.g., Ovukit: Bullivant et al, 2004;Ovusign: Gangestad et al, 2002;Clearplan: Graham, Janssen, & Sanders, 2000), measured cervical mucus (Burleson et al, 2002), or estrogen and progesterone levels (Sanders, Warner, Backstrom, & Bancroft, 1983) or their metabolites (Wilcox et al, 2004), but most studies employed backward or forward counts from Day 1 of menstruation (Table 1). Similar issues surround differences in the number of menstrual phases defined across a cycle (10 phases, Matteo & Rissman, 1984;6 phases, Bullivant et al, 2004;2 phases, Rosen & Lopez, 2009;Singh & Bronstad, 2001), the length of each phase (same length, Singh & Bronstad, 2001 or different lengths, Bullivant et al, 2004;Burleson et al, 2002), if data were broken down by cycle (Brown, Morrison, Calibuso, & Christiansen, 2008a) or averaged across women who contributed different numbers of cycles (Bullivant et al, 2004), and the number of cycles women were followed (usually only one but sometimes up to five cycles). Most researchers defined phases based on women's hormone profiles (broadly proliferative/follicular with high estrogen levels versus secretory/luteal with high estrogen and higher progesterone levels).…”
Section: Introductionmentioning
confidence: 96%
“…Some researchers employed physiological measurements to determine the LH surge (e.g., Ovukit: Bullivant et al, 2004;Ovusign: Gangestad et al, 2002;Clearplan: Graham, Janssen, & Sanders, 2000), measured cervical mucus (Burleson et al, 2002), or estrogen and progesterone levels (Sanders, Warner, Backstrom, & Bancroft, 1983) or their metabolites (Wilcox et al, 2004), but most studies employed backward or forward counts from Day 1 of menstruation (Table 1). Similar issues surround differences in the number of menstrual phases defined across a cycle (10 phases, Matteo & Rissman, 1984;6 phases, Bullivant et al, 2004;2 phases, Rosen & Lopez, 2009;Singh & Bronstad, 2001), the length of each phase (same length, Singh & Bronstad, 2001 or different lengths, Bullivant et al, 2004;Burleson et al, 2002), if data were broken down by cycle (Brown, Morrison, Calibuso, & Christiansen, 2008a) or averaged across women who contributed different numbers of cycles (Bullivant et al, 2004), and the number of cycles women were followed (usually only one but sometimes up to five cycles). Most researchers defined phases based on women's hormone profiles (broadly proliferative/follicular with high estrogen levels versus secretory/luteal with high estrogen and higher progesterone levels).…”
Section: Introductionmentioning
confidence: 96%
“…The lack of consensus across these studies may arise from three factors: first, some sleep studies have used ovarian hormones to determine menstrual phase [5,10], whereas others have used the more subjective measure of self-reported menstrual phase [11]. Second, some sleep studies have used objective measures of sleep, such as actigraphy and polysomnography, whereas others have used selfreport [5,10].…”
Section: Introductionmentioning
confidence: 97%
“…Self-reported sleep disturbance in women of reproductive age has been traditionally linked with menstrual cycle phase, and sleep disturbance remains a core symptom of premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) [4][5][6]. A physiologic link between ovarian hormones and sleep quality is plausible; however, evidence supporting a direct causal relationship remains sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has found additional evidence that links women's behavior with the different menstrual phases with the hormonal changes across these phases [33]. Previous studies indicate that females react to emotionally negative stimuli differently in the follicular compared to the luteal phase [26,34].…”
Section: Discussionmentioning
confidence: 99%